Deuterium magnetic resonance imaging of tumors using low-dose systemic deuterated water labeling - He, Mingchen; Duzen, Jill M.; Larus, Terri; Reavis, Hunter; Turowski, Steven G.; Feigin, Michael E.; Farthing, Don E.; Spernyak, Joseph A.; Buxbaum, Nataliya Prokopenko (Frontiers in Oncology, 2026)
BackgroundAlthough systemic 2H2O labeling is an attractive clinically relevant strategy for enhancing tumor imaging given relative ease of administration, gradual, slow ramp-up of labeling is preferable to avoid side effects, such as nausea and dizziness. Slow labeling periods are more easily tolerated but are suboptimal in the setting of cancer given the need to promptly diagnose and stage patients to initiate treatment. Hence, we sought to deploy low systemic concentrations of 2H2O in total body water (TBW) with short durations and low magnetic field strength to test clinically relevant experimental parameters conducive to clinical translation.MethodsHT-29 cells and KPC cells were used to establish subcutaneous and orthotopic murine tumor models, respectively. Systemic 2H2O administration was performed and TBW enrichment was confirmed via urine testing. All mice were imaged using the 7T MRI with a dual tuned (1H/2H) leg or body coil after 1, 3, or 7 days of systemic 2H2O labeling to 2 or 4% TBW (v/v).ResultsThe concentrations of 2H2O in urine samples closely reflected the target 2H2O enrichment level specified in the systemic labeling protocol. In all tested experimental schemas, there were no statistically significant differences in tumor-muscle contrast-to-noise ratio (CNR) and signal ratio among different labeling durations (p > 0.05), despite a significantly higher CNR at 4% compared with 2% (p = 0.02).ConclusionReasonable and stable imaging contrast between tumor and healthy tissue during the systemic labeling was achieved in this pre-clinical study, which offer preliminary indications of potential clinical translation of this imaging approach in cancer.